2015
DOI: 10.15283/ijsc.2015.8.2.134
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Spermatogenesis by Bone Marrow-derived Mesenchymal Stem Cells in Busulfan-induced Azoospermia in Hamste

Abstract: BackgroundBone marrow-derived mesenchymal stem cells (BM-MSCs) have potential of differentiation and they secrete anti-inflammatory cytokines and growth factors which make them appropriate for cell therapy.Aim of the WorkWere to evaluate the healing effect of BM-MSCs transplantation on germinal cells of busulfan-induced azoospermic hamsters.Material and MethodsIn the present experimental case control study, BM-MSCs were isolated from bone marrow of donor albino hamsters. Five mature male recipient hamsters rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
48
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 33 publications
(39 reference statements)
5
48
0
Order By: Relevance
“…However others reported that transplanted MSCs not only had the potency for differentiation into GCs (28), but also they could fully differentiate into sperm and regenerate spermatogenesis (27, 29). A recent study has showed the supportive role of BM-MSCs for recovery of spermatogenesis after transplantation into the testes of busulfan-induced infertile male hamsters (30). In the current study, we evaluated the fate of rat autologous BM-MSCs after transplantation into the testes of busulfan-induced infertile rats at 4, 6 and 8 weeks after transplantation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However others reported that transplanted MSCs not only had the potency for differentiation into GCs (28), but also they could fully differentiate into sperm and regenerate spermatogenesis (27, 29). A recent study has showed the supportive role of BM-MSCs for recovery of spermatogenesis after transplantation into the testes of busulfan-induced infertile male hamsters (30). In the current study, we evaluated the fate of rat autologous BM-MSCs after transplantation into the testes of busulfan-induced infertile rats at 4, 6 and 8 weeks after transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…Some in vitro studies on MSCs from different species have shown that under appropriate conditions and with proper inducers, MSCs had the capability to differentiate into male GCs (13, 18–24). Although a number of researchers believe that MSCs do not impact regeneration of testicular gametogenesis in infertile animal models (25, 26), other studies have shown that MSCs positively affect reconstruction of germinal epithelium and restoration of fertility (2730). …”
Section: Introductionmentioning
confidence: 99%
“…Although donor MSCs failed to complete meiosis, above studies emphasized the role of prior induction of MSCs with RA. Mesenchymal stem cell transplantation (MSCT) has resulted in an improved spermatogenesis index in the rat (Mehrabani et al ., and Rahmanifar et al ., ) and hamster (Tamadon et al ., ). Moreover, MSCs from higher order species also showed trans‐differentiation to pre‐meiotic ( STRA8 ) and post‐meiotic ( PRM1 ) germ cells after RA treatment for 14 days in culture (Wang et al ., ).…”
Section: Mesenchymal Stem Cell Transplantationmentioning
confidence: 97%
“…According to the literature, many studies have used the animal model of azoospermia for evaluating stem cell transplantation efficacy (Abuelhija et al, ; Azizollahi et al, ; Forand, Messiaen, Habert, & Bernardino‐Sgherri, ; Karimaghai et al, ; Koruji, Movahedin, Mowla, Gourabi, & Jabbary Arfaee, ; Lysiak, Turner, & Turner, ; Makoolati, Movahedin, Forouzandeh‐Moghadam, Naghdi, & Koruji, ; Rahmanifar et al, ; Tamadon et al, ; Vahdati, Fathi, Hajihoseini, Aliborzi, & Hosseini, ). The best model for this purpose should be depleting completely from all spermatogenic cells, especially spermatogonia because of the ability of division.…”
Section: Introductionmentioning
confidence: 99%